Digital and Financial Technology as a Support for the Growth of the Pancong Lumer MSME in Bojonegoro City - Melan Nuraini; Nanang Setiawan (Journal of Business Improvement, 2025)
This study aims to identify the role of digital and financial technology in supporting the development of the Pancong Lumer MSME in Bojonegoro City. The MSME sector plays a crucial role in the regional economy, and the application of Financial Technology is expected to provide solutions for overcoming the limitations of traditional financial access. The research employs a descriptive qualitative approach, collecting data through direct observation of the MSME operational activities, interviews with business owners and practitioners, and a review of relevant literature. The results indicate that, despite limitations in digital access, the implementation of Financial Technology has helped MSMEs manage finances more effectively, accelerate transactions, and improve access to information and broader markets. The contribution of this study is to provide deeper insights into how digital and financial technology can accelerate the development of MSMEs, particularly in the context of the increasingly evolving digital era